2020
DOI: 10.1016/j.heliyon.2020.e05114
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation trials of hop (Humulus lupulus L.) in semi-arid environments

Abstract: The recent developments in the market and craft beer industry in Italy have led to an increasing demand for local raw materials, such as barley malt and hops. Few works have been addressed to evaluate suitability and productivity of hop in semi-arid Italian environments. With this purpose, two experiments were carried out in 2018 and 2019, testing the suitability to cultivation of three commonly used hop varieties (Cascade, Chinook and Nuggett) in two typical semi-arid environments in Sicily. Phenological stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
2
19
0
1
Order By: Relevance
“…For this reason, studying hop phenology in new growing areas (e.g., southern European environments) can give useful directions for both selection of cultivars and temporal optimization of agronomic practices. To the best of our knowledge, just two studies, both in Italy, described the phenology of hops in the Mediterranean Basin [14,62]. Specifically, Rossini et al (2016) [14], in a three-year open field study, calculated the GDD accumulation for the onset of each of the four key growing stages (sprouting, flowering, development of cones and maturity of cones) of twenty hop cultivars in Central Italy.…”
Section: Phenologymentioning
confidence: 99%
See 3 more Smart Citations
“…For this reason, studying hop phenology in new growing areas (e.g., southern European environments) can give useful directions for both selection of cultivars and temporal optimization of agronomic practices. To the best of our knowledge, just two studies, both in Italy, described the phenology of hops in the Mediterranean Basin [14,62]. Specifically, Rossini et al (2016) [14], in a three-year open field study, calculated the GDD accumulation for the onset of each of the four key growing stages (sprouting, flowering, development of cones and maturity of cones) of twenty hop cultivars in Central Italy.…”
Section: Phenologymentioning
confidence: 99%
“…Spat' were the latest ones. Marceddu et al (2020) [62], in their two-year pot experiment, showed the progress of development stages for three hop varieties in the semi-arid environment of Sicily. They calculated GDD accumulation starting from transplanting date in which plants were at the second pair of leaves unfolded (phase 1.2, according to BBCH scale, [61]).…”
Section: Phenologymentioning
confidence: 99%
See 2 more Smart Citations
“…Rossini et al (2016Rossini et al ( , 2020 also stated that in central Italy the growth and yield of hop cultivars were affected significantly by the weather conditions, particularly by reduced precipitation and high temperatures. Marceddu et al (2020) reported a high variability of hop yield according to crop management in the region of Palermo in Italy.…”
Section: Discussionmentioning
confidence: 99%